Measuring the Impact of Targeting FcRn-Mediated IgG Recycling on Donor-Specific Alloantibodies in a Sensitized NHP Model - Manook, Miriam; Flores, Walter J.; Schmitz, Robin; Fitch, Zachary; Yoon, Janghoon; Bae, Yeeun; Shaw, Brian; Kirk, Allan; Harnois, Melissa; Permar, Sallie; Farris, Alton B.; Magnani, Diogo M.; et al. (Frontiers in Immunology, 2021)
Background: In transplantation, plasmapheresis and IVIg provide the mainstay of treatment directed at reducing or removing circulating donor-specific antibody (DSA), yet both have limitations. We sought to test the efficacy of targeting the IgG recycling mechanism of the neonatal Fc receptor (FcRn) using anti-FcRn mAb therapy in a sensitized non-human primate (NHP) model, as a pharmacological means of lowering DSA. Methods: Six (6) rhesus macaque monkeys, previously sensitized by skin transplantation, received a single dose of 30mg/kg anti-RhFcRn IV, and effects on total IgG, as well as DSA IgG, were measured, in addition to IgM and protective immunity. Subsequently, 60mg/kg IV was given in the setting of kidney transplantation from skin graft donors. Kidney transplant recipients received RhATG, and tacrolimus, MMF, and steroid for maintenance immunosuppression. Results: Circulating total IgG was reduced from a baseline 100% on D0 to 32.0% (mean, SD  10.6) on d4 post infusion (p<0.05), while using a DSA assay. T-cell flow cross match (TFXM) was reduced to 40.612.5% of baseline, and B-cell FXCM to 52.219.3%. Circulating total IgM and DSA IgM were unaffected by treatment. Protective immunity (anti-gB and anti-tetanus toxin IgG) was significantly reduced for 14d post infusion. Post-transplant, circulating IgG responded to anti-FcRn mAb treatment, but DSA increased rapidly. Conclusion: Targeting the FcRn-mediated recycling of IgG is an effective means of lowering circulating donor-specific IgG in the sensitized recipient, although in the setting of organ transplantation mechanisms of rapid antibody rise post-transplant remains unaffected.